Not So Beautiful Life: A Study on the Treatment of Black humour in Life is Beautiful - Rishad V (The Creative Launcher, 2021)
The Holocaust is one of the most tragic events ever happened in the human history. It was a systematic, bureaucratic and state sponsored persecution and murder of around six million Jews by the Nazi regime and its collaborators. Our memory of Holocaust, especially of the people belonging to this generation has been shaped more by popular representations, especially in films. The film Life is Beautiful directed by Robert Benigni portrayed the horror of Holocaust connotatively using black humour as its main medium. A short analysis of how Benigni uses black humour and other visual-cinema techniques in bringing out the terror of Holocaust among audience is studied in this article. Though the movie seems to fall under the genre comedy, it discusses connotatively the serious issues related to the life of Jews under Nazi regime without any use of violent images or scenes that reflect the real terrors of Holocaust.